Antibacterial activity of essential oils from different parts of plants against Salmonella and Listeria spp. (15th March 2023) - Meenu, Maninder; Padhan, Bandana; Patel, Madhumita; Patel, Rajkumar; Xu, Baojun
Highlights: Essential oils (EOs) exhibit potent biological activities including antimicrobial activity. Anti-listerial and anti-salmonella effects of EOs from various plant sources are discussed. The chemical composition and antibacterial activity of EOs varied based on plant sources. Major components of EO along with minor components exhibit synergistic antibacterial effects. EO presents complex and variable antibacterial mechanisms based on the type of bacteria. Abstract: Essential oils (EOs) have recently gained popularity as natural food preservatives due to their potent antibacterial activity against food pathogens. In this review, the antibacterial activity of EOs from various plant parts and sources against the most important food pathogens Salmonella and Listeria have been discussed. The antibacterial activity of EOs is attributed to their major and minor low-molecular weight terpenes, terpenoids, phenylpropenes and aliphatic components. The major compounds along with minor components of EO extracted from different parts of various plant species were found to be responsible for antibacterial activity. The combination of EO from different sources presented synergistic anti-listerial and anti-salmonella effects. EO combined with biopolymer and in nanoemulsion form presented significant antibacterial activity. The mode of antibacterial action by EO was complex and involves a series of event that has also been discussed in detail.